Natural Variation Identifies Multiple Loci Controlling Petal Shape and Size in Arabidopsis thaliana - Abraham, Mary C. (Public Library of Science, 2013)

(untitled)
Natural variation in organ morphologies can have adaptive significance and contribute to speciation. However, the underlying allelic differences responsible for variation in organ size and shape remain poorly understood. We have utilized natural phenotypic variation in three Arabidopsis thaliana ecotypes to examine the genetic basis for quantitative variation in petal length, width, area, and shape. We identified 23 loci responsible for such variation, many of which appear to correspond to genes not previously implicated in controlling organ morphology. These analyses also demonstrated that allelic differences at distinct loci can independently affect petal length, width, area or shape, suggesting that these traits behave as independent modules. We also showed that ERECTA (ER), encoding a leucine-rich repeat (LRR) receptor-like serine-threonine kinase, is a major effect locus determining petal shape. Allelic variation at the ER locus was associated with differences in petal cell proliferation and concomitant effects on petal shape. ER has been previously shown to be required for regulating cell division and expansion in other contexts; the ER receptor-like kinase functioning to also control organ-specific proliferation patterns suggests that allelic variation in common signaling components may nonetheless have been a key factor in morphological diversification.